Pattern and predictors of medical care received by hepatitis B carriers during pregnancy and after delivery. (March 2019) - Cheung, K.W.; Seto, M.T.Y.; Wong, D.; Mak, A.S.L.; So, P.L.; Lau, W.L.; Wang, W.; Kan, A.S.Y.; Lee, C.P.; Ng, E.H.Y.
Abstract: Objective: The objective of the study is to evaluate the pattern and predictors of medical care received by hepatitis B virus (HBV) carriers during pregnancy and after delivery in Hong Kong. Study design: The study is a retrospective analysis. Methods: Pregnant HBV carriers and their infants were followed up for 9–12 months after delivery. Face-to-face interviews were conducted to investigate what medical care they received for HBV before, during and after pregnancy. Results: Data were available for 412 HBV carriers. A total of 375 (91.0%) women were known HBV carriers before pregnancy. Routine antenatal screening picked out the remaining 37 (9.0%) HBV carriers; these women were younger, more likely to be smokers and had a lower level of education ( P < 0.05) than known HBV carriers. In total, 356 of 412 (86.4%) HBV carriers did not receive any medical care for HBV during pregnancy. Known HBV carrier status, history of medical check-up and the use of antiviral treatment before pregnancy were significant predictors for HBV medical care during pregnancy ( P < 0.05). The results show that 217 of 412 (52.6%) HBV carriers did not receive medical care for HBV after delivery. HBV medical care before pregnancy, use of antiviral treatment before pregnancy and a higher level of education were significant predictors for postpartum HBV medical care ( P < 0.05). Multivariate analysis showed that HBV medical care before pregnancy (odds ratio [OR], 7.73; 95% confidence interval [CI], 3.21–18.65; P < 0.001) and the use of antiviral treatment (OR, 5.02; 95% CI, 1.41–17.81; P = 0.013) were associated with medical care during pregnancy. Medical care before pregnancy was also associated with postpartum HBV medical care (OR, 5.05; 95% CI, 3.29–7.51; P < 0.001). Conclusions: A significant proportion of HBV carriers did not receive HBV-related medical check-ups during and after pregnancy in Hong Kong despite the majority being aware of their carrier status. Medical care before pregnancy predicted antenatal and postpartum HBV medical care. Highlights: There is a deficiency in multidisciplinary care for hepatitis B virus (HBV) carriers during pregnancy. There is a lack of continuity of HBV medical care after delivery. HBV medical care before pregnancy predicts the antenatal and postpartum medical care to be received.